A new chaotic attractor from 2D discrete mapping via border-collision period-doubling scenario - Zeraoulia Elhadj (Discrete Dynamics in Nature and Society)
The following map is studied: (x,y)→(1+a(|x|−y2)+y,bx). It is proved numerically that this model can display two different chaotic attractors, one is new and the other is a Lozi-type attractor. The new chaotic attractor is allowed via a border-collision period-doubling scenario, which is different from the classical period-doubling bifurcation.